Pengaruh Motivasi terhadap Kinerja Karyawan (Studi Kasus Mahasiswa Prodi Manajemen Fakultas Ekonomi Universitas Batanghari Jambi) - Ari Paramita S (Science of Management and Students Research Journal (SMS), 2020)
The main objective of this study is how the influence of motivation on the employee’s marketing performance in PT Nutricia Sari Husada Jambi period 2014-2018. The object of this analysis at the office PT Nutricia Sari Husada Jambi. The study samples used as 37 (thirty seven) all of marketing employees who work at PT Nutricia Sari Husada. The study method used is descriptive of quantitative independent with motivation. While variable dependent is employee’s performance. Analytical tool used is reability test of multiple linear regression equation, test t and test f, classic assumption test (normality, multicollinearity and heteroscedasticity), correlation, coefficient and determination.Based on the results of linear regression analysis show the equation Y = a + b X+ e. With a correlation value test (R2) 0,578 that means the correlation quite strong, value of determination (R) 31,5% while the rest influenced by others careful variable and thitung 4,191 > ttabel, 1,68957The Conclusions of this study indicate that motivation have a significant effect on performance of employees in the performance, whereas motivation variable has significant effect to employee’s marketing performance in The PT. Nutricia Sari Husada Jambi.